El educador como agente de felicidad: una reflexión desde la psicología humanístico-cristiana - Maurial Chávez, Iván (2010)
The author, based on his personal experience and on the foundations of humanistic & christian psychology, reflects about the in-depth meaning of education as a routine that goes beyond the simple fact of transmitting knowledge enhanced by the use of new technologies. The educator should become a prometer of happiness when guiding a value-building teaching process towards personal growth focused on the search of the meaning of life. The author also points out the pertinence of having knowledge on logotherapy and transactional analysis, as well as the necessity to regain the values provided by religion to base alife on values.